A sociological analysis of the experiences of Zimbabwean teachers in South Africa: the case of KwaZulu-Natal townships and township secondary schools - Daki, Andile Lebohang (Rhodes University, Faculty of Humanities, Department of Sociology)
This thesis seeks to understand the social and cultural experiences of Zimbabwean teachers, as foreigners, in KwaZulu-Natal townships, and KwaZulu-Natal township secondary schools, in South Africa. It examines the ways in which Zimbabwean teachers negotiate the social, cultural, and institutional milieu of KwaZulu-Natal townships and secondary schools. In doing so, the thesis draws upon social interface theory, as this theory facilitates an examination and understanding of the ways in which the Zimbabwean teachers interpret the spaces (and lifeworld) of South Africans and, simultaneously, navigate their way in and through these spaces along social and cultural interfaces. While the focus is on the perspectives and practices of the Zimbabwean teachers, the thesis recognises and shows that their socio-cultural experiences are constituted and configured in significant ways by their daily encounters with South Africans. The fieldwork for the thesis involved primarily in-depth interviews with thirty Zimbabwean teachers residing in six selected KwaZulu-Natal townships (and teaching at six different secondary schools), as well as fifteen South African teachers, five school administrators and thirty other South African citizens. The sample of Zimbabwean teachers was stratified in relation to the different townships, as well as gender and the number of years teaching in South Africa, so as to investigate whether and how these variables may configure the socio-cultural experiences of these teachers. A consideration of variation in the number of years of teaching in South Africa in particular allowed for an examination of possible shifts in socio-cultural experiences over time, as negotiation along interfaces is an ongoing and contingent process. The findings demonstrate a range of experiences and challenges faced by Zimbabwean teachers in KwaZulu-Natal (with regard to both township and school life), some of which they share with South African teachers but many of which are unique to them. At the same time, there are important differences amongst Zimbabwean teachers in relation to how they interface with South African citizens and teachers. While some teachers negotiate local spaces through active socialising and assimilating into the lifeworld (township life of South Africans and the institutional culture of township schools), other teachers move through the space by way of isolation, withdrawal, and alienation. In general, in terms of adjusting to the lifeworld of South Africans in KwaZulu-Natal townships and schools, Zimbabwean teachers pursue different routes which, in the end, made sense to them and about which they express some degree of personal comfort.,Lo mbhalo wobuhlakani uzama ukuqonda inhlalo kanye namasiko abahlangabezana nako othisha baseZimbabwe njengabantu bokufika emalokishini akwaZulu-Natal, kanye nasezikoleni zamabanga athe thuthu zasemalokishini akwaZulu-Natal eNingizimu-Afrika. Uhlolisisa izindlela labo thisha ababonisana ngazo ngamasiko kanye nenhlalakahle yasezikoleni zasemalokishini akwaZulu-Natal. Ngokwenzanjalo, lo mbhalo udonsa umhlahlandlela wenhlalakahle nokuhlangana ngoba ukungena kwabo endaweni yakwaZulu-Natal, labo thisha bahumusha indawo baphinde babonisane bachushisane ngenqubekela phambili yabo nangenhlalo namasiko abahlangabezana nawo. Ukuhlanganisa othisha baseNingizimu-Afrika nezakhamuzi kumele kusebenzisane ngokulingana. Abahlangabezana nakho kwakhiwa ngokubambisana phakathi kwabaseZimbabwe kanye nabaseNingizimu-Afrika ukuze izwi labaseNingizimu-Afrika lingagqibeki ngoba sekunakekelwa kakhulu abseZimbabwe. Umsebenzi wasensimini walo mbhalo wobuhlakani uhlanganisa ucwaningo kothisha abangani-30 baseZimbabwe abahlala ezindaweni ezingu-6 ezikhethekile ezisemalokishini akwaZulu-Natal, nothisha abayi-15 baseNingizimu-Afrika kanye nabaphathi bezikole abayi-5. Kubuye kwenziwa ucwaningo kwizakhamuzi ezingama-30 zaseNingizimu-Afrika. Isampula lihlanganiswe ngokubuka indawo lapho aphuma khona umuntu, kanye neminyaka aseyifundisile eNingizimu-Afrika. Ucwaningo lubukisise kakhulu indlela ababuka ngayo inhlalakahle namasiko kube kubukisiswa nenani leminyaka aseyifundisile umuntu ngamunye ukuze kuhlolisiswe izinguquko zokuxoxisana ezidalwe yisikhathi asihlalile umuntu phakathi kothisha abasebancane nalabo asebekhulile. Imiphumela yocwaningo iveza iznselele ezahlukene ababhekene nazo othisha baseZimbabwe njengoba bengabahlali baseNingizimu-Afrika. Ezinye zalezi nselele ziqhamuka ngokwehlukana kwemiphakathi kwabaseZimbabwe kanye nabaseNingizimu-Afrika. Ngokunjalo kunomehluko obalulekayo kothisha baseZimbabwe mayelana nendlela ukuxoxisana nokubonisana okuqhubeka ngayo. Kukhona labo ukungena bathi khaxa emiphakathini nasezimpilweni abakuzo eNingizimu-Afrika nasezikoleni abakuzo namasiko nenhlalakahle yakulezo zindawo ngakolunye uhlangothi abanye othisha bazithole bephila njengenhlwa bephila ngabodwana eNingizimu-Afrika. Kodwa ekugcineni kwakho konke, lolu cwaningo luthola ukuthi othisha baseZimbabwe ezikoleni zasemalokishini akwaZulu-Natal lapha eNingizimu-Afrika bazakhela impilo eyenza umuntu ngamunye azizwe ehlaliseke kahle eNingizimu- Afrika ngendlela ephelele nethokomalisa yena ngo kwakhe.
Keywords: Xenophobia -- South Africa KwaZulu-Natal; Teachers, Foreign -- South Africa KwaZulu-Natal; Zimbabweans -- South Africa KwaZulu-Natal; Teachers, Foreign Social conditions; Marginality, Social; Culture conflict -- South Africa KwaZulu-Natal